(untitled) (MATEMATIKA, 2020)
Aging is a good indicator in demographic and health areas as the lifespan of the elderly population increases. Based on the government’s Economic Outlook 2019, it was found that an aging population would increase the government pension payments as the pensioners and their beneficiaries have longer life expectancy. Due to mortality rates decreasing over time, the life expectancy tends to increase in the future. The aims of this study are to forecast the mortality rates in the years 2020 and 2025 using the Heligman-Pollard model and then analyse the effect of mortality improvement on the pension cost (annuity factor) for the Malaysian population. However, this study only focuses on estimating the annuity factor using life annuities through the forecasted mortality rates. The findings indicated that the pension cost is expected to increase if the life expectancy of the Malaysian population increases due to the aging population in the near future. Thus, to reduce pension costs and help the pensioners from insufficient financial income, the government needs to consider an extension of the retirement age in future.